Features project management adaptive technological systems fertilization, soil preparation and sowing of crops - Луб, Павло Миронович (Eastern-European Journal of Enterprise Technologies, 2012)
The background adaptation process operations of fertilization, soil-tillage and sowing of crops to the changing conditions of the project environment are defined. The main task of developing methods and models of project management such adaptive technological systems are identifies